FORMULATION DEVELOPMENT AND EVALUATION OF FAST DISSOLVING FILMS OF EBASTINE - TORGAL, TEJASVI; BORKAR, SHWETA; BHIDE, PRASHANT; ARONDEKAR, ASMITA (International Journal of Current Pharmaceutical Research, 2020)
Objective: To overcome the limitations of fast dissolving tablets, a novel fast dissolving film of ebastine was formulated for attaining quick onset of action, aiding in the enhancement of bioavailability favorable in severe conditions of allergies. Methods: Films of ebastine were prepared by the solvent casting method using hydroxypropyl methylcellulose E-15, hydroxypropyl methylcellulose K-4 as a film base with different concentrations of crospovidone as superdisintegrant and polyethylene glycol-400 as a plasticizer. Further physical characteristics such as uniformity of weight, thickness, and drug content uniformity, tensile strength, folding endurance, percentage elongation, surface pH, disintegration and in vitro drug release were evaluated. Results: The optimized formulations with film base hydroxypropyl methylcellulose E-15 and hydroxypropyl methylcellulose K-4 containing 8% crospovidone showed 99.34 % and 97.42 % of maximum cumulative percentage release respectively exhibiting first order kinetics. However, no significant change was observed in stability studies. Conclusion: The concept of formulating fast dissolving films of ebastine offers a suitable approach in exhibiting rapid onset of action with improved delivery.